A Comprehensive Analysis of Citrus Tristeza Variants of Bhutan and Across the World - Ghosh, Dilip Kumar; Kokane, Amol; Kokane, Sunil; Mukherjee, Krishanu; Tenzin, Jigme; Surwase, Datta; Deshmukh, Dhanshree; Gubyad, Mrugendra; Biswas, Kajal Kumar (Frontiers in Microbiology, 2022)
Mandarin orange is an economically one of the most important fruit crop in Bhutan. However, in recent years orange productivity has dropped due to severe infection of citrus tristeza virus (CTV) associated with the gradual decline of citrus orchards. Although the disease incidence has been reported, very limited information is available on genetic variability among the Bhutanese CTV variants. This study used RT-PCR to detect CTV in collected field samples and recorded disease incidence up to 71.11 % in Bhutan’s prominent citrus growing regions. To elucidate the extent of genetic variabilities among the Bhutanese CTV variants, we targeted four independent genomic regions (5´ORF1a, p25, p23, and p18,) and analyzed a total of 64 collected isolates. These genomic regions were amplified and sequenced for further comparative bioinformatics analysis. Comprehensive phylogenetic reconstructions of the GenBank deposited sequences, including the corresponding genomic locations from 53 whole-genome sequences, revealed unexpected and rich diversity among Bhutanese CTV variants. A resistant-breaking (RB) variant was also identified for the first time from the Asian subcontinent. Our analyses unambiguously identified five (T36, T3, T68, VT, and HA16-5) major, well-recognized CTV strains. Bhutanese CTV variants form two additional newly identified distinct clades with higher confidence, B1 and B2, named after Bhutan. The origin of each of these nine clades can be traced back to their root in the north-eastern region of India and Bhutan. Together, our study established a definitive framework for categorizing global CTV variants into their distinctive clades and provided novel insights into multiple genomic region-based genetic diversity assessments, including their pathogenicity status.